2015
DOI: 10.1002/jbmr.2512
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Fat Depots and Marrow Adiposity Are Associated With Skeletal Deficits and Insulin Resistance in Long-Term Survivors of Pediatric Hematopoietic Stem Cell Transplantation

Abstract: Allogeneic hematopoietic stem-cell transplantation (alloHSCT) survivors treated with total body irradiation (TBI) exhibit bone deficits and excess adiposity, potentially related to altered mesenchymal stem cell differentiation into osteoblasts or adipocytes. We examined associations among fat distribution, bone microarchitecture, and insulin resistance in alloHSCT survivors after TBI. This was a cross-sectional observational study of 25 alloHSCT survivors (aged 12–25 years) a median of 9.7 (4.3–19.3) years aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
92
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(94 citation statements)
references
References 67 publications
2
92
0
Order By: Relevance
“…Calf muscle and fat CSA (mm 2 ) were assessed at the 66 % diaphyseal site. As previously described [20, 21], pQCT measure of muscle density (g/cm 3 ) was also obtained. Scans were analyzed using Stratec software, version 6.20.…”
Section: Methodsmentioning
confidence: 99%
“…Calf muscle and fat CSA (mm 2 ) were assessed at the 66 % diaphyseal site. As previously described [20, 21], pQCT measure of muscle density (g/cm 3 ) was also obtained. Scans were analyzed using Stratec software, version 6.20.…”
Section: Methodsmentioning
confidence: 99%
“…Importantly, our patients with MetS were not overweight or obese; high BMI is thus not a sensitive trigger for investigation of MetS after HSCT. Mostoufi-Moab et al [44] reported that allogeneic HSCT survivors treated with TBI exhibit markedly increased marrow adiposity and increased visceral adipose tissue with relatively normal BMI. These survivors demonstrated sarcopenic obesity with insulin resistance, a recognized risk factor for MetS in this population.…”
Section: Discussionmentioning
confidence: 99%
“…There is building evidence of the effects on increased fat on abnormal bone mass, likely to be mediated by adipocytokines like leptin [29]. The association of increased fat in chronic disease and increased marrow adiposity due to a state of GH resistance and reflective of osteoblastogenesis may also be another mechanism in lower bone formation [30]. …”
Section: Pathophysiology Of Secondary Osteoporosismentioning
confidence: 99%
“…There may be a place to incorporate evaluation with bone histomorphometry as a form of monitoring in those treated with bisphosphonate to guide duration of therapy. Newer modalities of bone imaging including high-resolution pQCT and micro-MRI [30,46] may allow assessment of bone microarchitecture, and these findings may closely correlate with bone biopsy results [47], although such imaging modalities are currently only available as research tools. …”
Section: Assessment Of Bone Healthmentioning
confidence: 99%